Antibiotic resistance, plasmids, and virulence-associated markers in human strains of Campylobacter jejuni and Campylobacter coli isolated in Italy - Garcia-Fernandez, Aurora; Janowicz, Anna; Marotta, Francesca; Napoleoni, Maira; Arena, Sergio; Primavilla, Sara; Pitti, Monica; Romantini, Romina; Tomei, Fiorella; Garofolo, Giuliano; Villa, Laura (Frontiers in Microbiology, 2024)
Campylobacteriosis, a prevalent foodborne gastrointestinal infection in Europe, is primarily caused by Campylobacter jejuni and Campylobacter coli, with rising global concerns over antimicrobial resistance in these species. This study comprehensively investigates 133 human-origin Campylobacter spp. strains (102 C. jejuni and 31 C. coli) collected in Italy from 2013 to 2021. The predominant Multilocus Sequence Typing Clonal complexes (CCs) were ST-21 CC and ST-206 CC in C. jejuni and ST-828 CC in C. coli. Ciprofloxacin and tetracycline resistance, mainly attributed to GyrA (T86I) mutation and tet(O) presence, were prevalent, while erythromycin resistance was associated with 23S rRNA gene mutation (A2075G), particularly in C. coli exhibiting multidrug-resistant pattern CipTE. Notable disparities in virulence factors among strains were observed, with C. jejuni exhibiting a higher abundance compared to C. coli. Notably, specific C. jejuni sequence types, including ST-21, ST-5018, and ST-1263, demonstrated significantly elevated counts of virulence genes. This finding underscores the significance of considering both the species and strain-level variations in virulence factor profiles, shedding light on potential differences in the pathogenicity and clinical outcomes associated with distinct C. jejuni lineages. Campylobacter spp. plasmids were classified into three groups comprising pVir-like and pTet-like plasmids families, exhibiting diversity among Campylobacter spp. The study underscores the importance of early detection through Whole Genome Sequencing to identify potential emergent virulence, resistance/virulence plasmids, and new antimicrobial resistance markers. This approach provides actionable public health data, supporting the development of robust surveillance programs in Italy.